ESTIMASI KAPASITAS ASIMILASI PERAIRAN BERDASARKAN STANDAR EFFLUENT LIMBAH NITROGEN DAN FOSFOR BUDIDAYA UDANG - Abdul Muqsith; Nuddin Harahab; Mohammad Mahmudi; Muhammad Fadjar (Faculty of Science and Technology University Ibrahimy, 2018)
This research was conducted in May 2018 in the coastal area of ​​Banyuputih Subdistrict, Situbondo Regency, East Java with the aim of estimating the volume of seawater available in coastal waters and the capacity of coastal waters in assimilating N and P waste load based on N and P effluent standards for cultivation shrimp. The results showed that the coastal waters of Banyuputih had a volume of water available for dilution of N and P wastes of 43,198,298 m3. The maximum N and P waste load that can be assimilated by water according to the standard effluent of N waste for shrimp farming is 172, 8 tons and for the P waste load is 17.28 tons. The results of this study can be used as a reference in determining the environmental carrying capacity of coastal waters in the development of intensive shrimp ponds in the study area.